1986
DOI: 10.1192/bjp.148.4.414
|View full text |Cite
|
Sign up to set email alerts
|

Brain Indicators of Altered Attention and Information Processing in Schizophrenic Patients

Abstract: Late components of brain event-related potentials reflect aspects of selective attention, stimulus evaluation, and possibly memory update mechanisms. Several of these components were measured during an auditory target detection task, performed by 20 schizophrenic and 20 normal subjects. Both the amplitude of those components and a more general late amplitude measure were significantly reduced in schizophrenics, for both target and non-target stimuli. One general late amplitude measure, from the scalp vertex, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 18 publications
3
16
1
1
Order By: Relevance
“…There was a strong variation on its values; this could be also due to the overlapping slow wave which was not separately con sidered when integrating the P300 curve. We did not observe an influence of neuroleptics on P300 latency, a finding consistent with other studies [16,19,40] and on its duration and area. No relationship was observed between clinical ratings and P300 parameters.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…There was a strong variation on its values; this could be also due to the overlapping slow wave which was not separately con sidered when integrating the P300 curve. We did not observe an influence of neuroleptics on P300 latency, a finding consistent with other studies [16,19,40] and on its duration and area. No relationship was observed between clinical ratings and P300 parameters.…”
Section: Discussionsupporting
confidence: 81%
“…We could not reproduce the findings of Blackwood et al [19] in relation to the BPRS and of Pfefferbaum et al [17] in relation to the MMS. A relationship between negative symptoms and P300, as proposed by Barrett et al [40], could also not be observed.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The notion of smaller event-related potential (ERP) amplitudes in schizophrenics compared to controls has a long tradition (Barrett, McCallum, & Pocock, 1986;Blackwood et al, 1987;McCarley et al, 1993;Roth & Cannon, 1972; see also review by Cohen, 1991). The smaller amplitudes of negative components (such as the auditory N1, the visual N1 and N2 (e. g., Bruder et al, 1999), the mismatch negativity, MMN, or the contingent negative variation, CNV) and of the P300 have been interpreted as indicating dysfunction of the cognitive processes associated with them.…”
Section: Introductionmentioning
confidence: 99%
“…P300 variability among normal subjects can be categorized in the interindividual or intraindividual variability. For the interindividual variability, the most studied and distinguished factor is the age factor [6][7][8], where the greatest variability appeared in subjects younger than 50 years of age and older than 55, but it was much smaller in subjects between 30 and 40 years of age. While the most familiar example is the intraindividual variability, the fact is that the given probability of the target stimulus manifestation can change the amplitude and latency of the P300 complex, because in the repeated recordings, the changes in the probability of the target stimulus manifestation changed the amplitude and also the latency of the P300 wave complex [5,9,10].…”
Section: Discussionmentioning
confidence: 99%